Chronic Autoimmune Epithelitis - Sjogren's Syndrome and Other Autoimmune Diseases of the Exocrine Glands 2019
DOI: 10.5772/intechopen.83821
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren’s Syndrome as an Ocular Problem: Signs and Symptoms, Diagnosis, Treatment

Abstract: Sjögren's syndrome (SS) is an autoimmune disease of exocrine glands, which is characterized by dry mouth and dry eye, though ocular disturbances, such as dry eye disease, may be the first sign of the problem. In pathogenesis of SS, activated T-cells and B-cells infiltrate the lacrimal glands and autoimmune process leading to cell destruction. This process causes hyposecretion of tears and aqueous-deficient dry eye disease. Evaporative dry eye disease is connected with Meibomian gland dysfunction (MGD) and/or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 119 publications
(271 reference statements)
0
3
0
Order By: Relevance
“…Aqueous layer deficiency is the most common reason of dry eye and is classified into two groups: Sjögren Syndrome dry eye and non-Sjögren Syndrome dry eye [69,70].…”
Section: Aqueous Layer Disturbancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Aqueous layer deficiency is the most common reason of dry eye and is classified into two groups: Sjögren Syndrome dry eye and non-Sjögren Syndrome dry eye [69,70].…”
Section: Aqueous Layer Disturbancesmentioning
confidence: 99%
“…Sjögren's syndrome (SS) is a rheumatic autoimmune disease in which exocrine glands (salivary and lacrimal glands) are involved that results in clinical symptoms of dry mouth and dry eye. SS can be primary-pSS (without any other accompanying symptoms) or secondary-sSS (with other autoimmune diseases: systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), polyarteritis nodosa, systemic sclerosis, granulomatosis with polyangiitis (GPA), primary biliary cholangitis (PBC), mixed connective tissue disease, occult thyroid eye disease) [69,71]. Some studies demonstrated coincidence of dry eye disease (DED) and SS in 46.7% cases [69,72].…”
Section: Aqueous Layer Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation